Dynamic Structural Behavior of Monopile Support Structure for 15 MW Offshore Wind Turbine During Different Phases of Operation - Sajid Ali; Muhammad Waleed; Daeyong Lee (Journal of Marine Science and Engineering)
The structural integrity of offshore wind turbine monopiles is critical for ensuring operational stability and long-term performance under varying environmental and aerodynamic loads. However, transient load conditions during different operational phases, such as start, normal stop, and emergency stop, can significantly impact structural behavior, influencing fatigue life and dynamic stability. This study investigates the dynamic structural response of a 15 MW offshore wind turbine monopile, incorporating modal analysis and transient simulations to assess deflection, forces, moments, and rotational displacements at the mud-line. The modal analysis revealed natural frequencies of 0.509492 Hz, 1.51616 Hz, and 3.078425 Hz for the blade’s flap-wise modes, while side-to-side modes for the combined tower and monopile structure were identified at 0.17593 Hz, 0.922308 Hz, and 1.650862 Hz. These frequencies are crucial in evaluating resonance risks and ensuring dynamic stability under combined aerodynamic and hydrodynamic forces. The transient analysis demonstrated that lateral force (Fy) variations peaked at −2500 kN during emergency stop, while moment fluctuations (My) reached ±100,000 kNm, reflecting the monopile’s high dynamic sensitivity under sudden aerodynamic unloading. Rotational displacements also showed significant variations, with θx oscillating up to ±0.0009 degrees and θy between −0.0022 and −0.0027 degrees. These findings provide valuable insights into optimizing monopile design to mitigate resonance effects, improve fatigue performance, and enhance structural resilience for large-scale offshore wind turbine support systems.